Perdão e crescimento pós-traumático no âmbito do divórcio: uma explicação pautada nos valores humanos - Couto, Ricardo neves (2017)
This dissertation aimed to know the extent to which human values explain forgiveness and post-traumatic growth (PTG) in the context of divorce. Two studies were carried out. In Study 1 aimed to gather evidence of validity and internal consistency of the Cuestionario de Perdón en Divorcio-Separación (CPD-S) with a sample of 200 individuals (ages 19 to 71 years, M = 38.42, SD = 11,51) who have already gone through the divorce process. The majority resided in the states of Paraíba (29.32%) and Piauí (27.21%) and were equally distributed between the sexes. All responded to CPD-S and sociodemographic issues. The results of the exploratory factorial analysis indicated the extraction of a single factor, composed of 4 items and an internal consistency (Cronbach's alpha = .78), which was also favorable. In Study 2 had as objectives to test the structure of CPD-S, to identify the influence of sociodemographic variables on forgiveness and to know the predictive power of human values in forgiveness and PTG in the scope of divorce. The sample consisted of 200 individuals (ages ranging from 18 to 84 years old, M = 42.02, SD = 11.99) who had already undergone divorce proceedings, mostly residing in the state of Piauí (44.12%) and Women (75%). They lived on average 10.56 years (SD = 7.48) with the former spouse, being on average 8.63 years (SD = 8.19) divorced and the biggest part (66.5%) had a divorce consensual, 58% said they are not in another love relationship. About religiosity level, in a scale that could vary between 1 = nothing / little and 7 = a lot, the participants' mean was 4.98 (SD = 1.83). All of them responded to the instruments of the first study in addition to the Basic Values Questionnaire and the Posttraumatic Growth Inventory. The result of the confirmatory factorial analysis shows good indexes of adjustment quality of the CPD-S, confirming its unifatorial structure. The predictive power of human values for forgiveness and PTG can be verified through Pearson's correlation and linear regressions, noting that only the interactive subfunction explains the forgiveness (β = .17, p < .05 ) And that the normative subfunction (β = .20, p < .01) and promotion (β = .24, p < .01) are the best predictors of PTG. It is still possible to identify the possible influences of sociodemographic variables in the levels of forgiveness and PTG. Through Pearson's correlations, a positive relationship of forgiveness with time of divorce and level of religiosity was observed, through the test t, it was identified that those who had a consensual divorce granted more pardon and through ANOVA it was verified that older people show greater magnitudes of forgiveness. Regarding PTG, the results indicate that there are positive and statistically significant correlations, only, between PTG and divorced time and religiosity level. The other sociodemographic variables considered in the study had no influence on the scores. The results suggest that the individual who endorses values of the interactive subfunction, focusing on the quality of relationships presents higher rates of forgiveness, for worrying and nurturing feelings of care and affection with the other. And people who prioritize the values of the normative subfunction, recognizing the existence of a superior entity and affirmation of their faith to overcome, and those of the achievement subfunction, requiring high self-esteem and demonstration of competencies, experience positive changes after divorce. In view of the objectives achieved, it is hoped that this dissertation contributes with the growing literature of forgiveness, providing a measure with assured psychometric qualities and with the productions about the PTG, with scientific evidences on the themes. In addition, it demonstrates the centrality of human values in the studies of social psychology, in the explanation of psychosocial phenomena that promote health, social harmony and adaptation to divorce.